An Efficient Certificate-Based Aggregate Signature Scheme for Internet of Drones. (15th January 2022) - Khan, Muhammad Asghar; Ullah, Insaf; Alsharif, Mohammed H.; Alghtani, Abdulaziz H.; Aly, Ayman A.; Chen, Chien-Ming
Abstract : Internet of drones (IoD) is a network of small drones that leverages IoT infrastructure to deliver real-time data communication services to users. On the one hand, IoD is an excellent choice for a number of military and civilian applications owing to key characteristics like agility, low cost, and ease of deployment; on the other hand, small drones are rarely designed with security and privacy concerns in mind. Intruders can exploit this vulnerability to compromise the security and privacy of IoD networks and harm the information exchange operation. An aggregate signature scheme is the best solution for resolving security and privacy concerns since multiple drones are connected in IoD networks to gather data from a certain zone. However, most aggregate signature schemes proposed in the past for this purpose are either identity-based or relied on certificateless cryptographic methods. Using these methods, a central authority known as a trusted authority (TA) is responsible for generating and distributing secret keys of every user. However, the key escrow problem is formulated as knowing the secret key generated by the TA. These methods are hampered by key distribution issues, which restrict their applicability in a variety of situations. To address these concerns, this paper presents a certificate-based aggregate signature (CBS-AS) scheme based on hyperelliptic curve cryptography (HECC). The proposed scheme has been shown to be both efficient in terms of computation cost and unforgeable while testing its toughness through formal security analysis.